The relationship of health beliefs on the stage of mammography behavior adoption amongst women in Kuantan, Pahang - Ramli, Hanis Aisyah; Moey, Soo Foon; Abdul Mutalib, Aainah Mardhiah (Asia Pacific Organization for Cancer Prevention (APOCP), 2019)
Background: Breast cancer (BC) awareness is relatively poor among Malaysian women indicated by the presence of BC at a late stage and the low rate of mammography screening. Only a few theoretically based studies have been conducted on Malaysian women’s participation in mammography. Therefore, the objective of this study is to use health belief model (HBM) and stage of change model (SCM) to determine the relationship between health beliefs on the behavioural adoption of mammography amongst women in Kuantan, Pahang. Methods: Five hundred and twenty women were randomly selected to complete the survey. Data were analyzed using multinomial logistic regression (MLR) to ascertain the multivariate relationships between health beliefs and stage of mammography behavioural adoption. Results: The MLR test indicates that there is no significant difference in perceived severity, benefits, motivator factors and cues to action between participants in the action stage and the maintenance stage. However, significant differences existed in perceived severity, susceptibility, motivator factors and self-efficacy between the pre-contemplation, relapse and contemplation stage to that of the referenced (maintenance) stage of mammography adoption. Conclusion: Women in the action stage are more likely to progress towards maintenance stage as they perceived breast cancer as a disease that leads to death and that mammogram screening is beneficial in detecting the disease at an early stage. However, women in the pre-contemplation, relapse and contemplation stage are found unlikely to move towards the maintenance stage as they perceived their risk of getting breast cancer is low.